Brachial plexopathy in breast cancer: is it radiation related? An analysis technique and dose volume parameters to brachial plexus in breast cancer radiotherapy - Kunheri, Beena; Radhakrishnan, Anand; Stephen, Toyce; Mon, Renil; Menon, Anjali (International Journal of Research in Medical Sciences, 2017)
Background: Brachial plexus dysfunction is a rare but well-recognized complication of breast cancer surgery and radiotherapy. Most of the time it presents as paraesthesia of the arm. In an earlier publication Dan Lundstedt et al from Sweden, quantitatively assessed the radiation related brachial plexopathy (mainly paraesthesia) with the help of dose volume histograms and its co relation between patient reported paraesthesia. Paraesthesia was reported by 25% after radiation therapy to the supraclavicular fossa, with a V40 Gy 13.5 cm3 and maximum dose to brachial plexus (Dmax) was not found to correlate with paraesthesia. In order to predict the risk brachial plexopathy in our patients we decided to analyze the dose volume parameters for brachial plexus in carcinoma breast patients treated at our institution with modern radiotherapy techniques. Methods: Twenty five consecutive patients who received post mastectomy radiation during the period September 2015 to January 2016 with a dose of 50Gy in 25 fractions were included for this analysis. Brachial plexus contoured using RTOG guidelines, and dose volume parameters for brachial plexus were documented from the existing treatment plans. Results: The maximum dose to the brachial plexus ranged from 5045cGy to 5679cGy with a mean value of 5312.8cGy. The mean dose received by the brachial plexus ranged from 3093cGy to 4714cGy and the mean value was 4137.28cGy. Volume receiving 40Gy, that is V40, ranged from 2.0078cc to 11.56cc with a mean value of 7.57cc. Conclusions: Maximum dose and V40 Gy values were well below the tolerance limit of plexus, and hence post mastectomy irradiation with modern techniques is unlikely to produce significant brachial plexus neuropathy.